2018
DOI: 10.1590/0102-311x00006617
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da exposição a poluentes do ar na saúde das crianças de Cuiabá, Mato Grosso, Brasil

Abstract: Efeitos da exposição a poluentes do ar na saúde das crianças de Cuiabá, Mato Grosso, BrasilEfectos de la exposición a contaminantes del aire en la salud de los niños de Cuiabá, Mato Grosso, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
1
13
0
6
Order By: Relevance
“…20 The direct effects of this exposure may occur through agents that cross the pulmonary epithelium in the circulation, such as gases and possibly ultrafine particles (< 0.1 µ), along with soluble constituents Subsequently, this may contribute towards a systemic inflammatory state, which may, in turn, be able to activate hemostatic pathways, impair vascular function and accelerate atherosclerosis. 25 The present study had some limitations, and the way in which pollutant concentrations were estimated was one of them. This was done through mathematical modeling and may have provided incorrect data.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…20 The direct effects of this exposure may occur through agents that cross the pulmonary epithelium in the circulation, such as gases and possibly ultrafine particles (< 0.1 µ), along with soluble constituents Subsequently, this may contribute towards a systemic inflammatory state, which may, in turn, be able to activate hemostatic pathways, impair vascular function and accelerate atherosclerosis. 25 The present study had some limitations, and the way in which pollutant concentrations were estimated was one of them. This was done through mathematical modeling and may have provided incorrect data.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, use of data estimated through the CCATT-BRAMS model, which has already been implemented in other studies, may form an alternative for studies on the effects of exposure to fine particulate matter on human health, such as in relation to respiratory and cardiovascular diseases. [22][23][24][25]…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the periods with the highest concentration of PM 2.5 are the ones that present the greatest risk to the population and that meteorological factors have an influence on the increase in pollutant concentration, the rules presented in Table 6 could give warning indications for the increase in pollutant concentration. In Brazil, the studies by César et al (2016) and Machin and Nascimento (2018) show the influence of the 5 μg/m 3 increase in the concentrations of PM 2.5, resulting in increases between 20 and 38% in the risk of hospitalization due to pulmonary complications.…”
Section: Stationmentioning
confidence: 99%
“…According to the Environmental Company of São Paulo State (CETESB, 2019), the main air pollutants regulated by the National Environment Council (CONAMA) are: coarse inhalable particles (PM 10 ), fine inhalable particles (PM 2.5 ), carbon monoxide (CO), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), ozone (O 3 ), total suspended particles (TSP), smoke (SMO), and lead (Pb), the latter three being monitored only in specific situations. Studies on the effects of pollution on health (POLEZER et al, 2018;MACHIN;NASCIMENTO, 2018;SEINFELD;PANDIS, 2016;NODARI;SALDANHA, 2016) show that exposure to fine particulate matter (PM 2.5 ) can cause respiratory problems and even premature deaths, since it penetrates deeply into the respiratory system, reaching the pulmonary alveoli and the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have evaluated the adverse effects of air pollutants on the health of the population, including mortality rates, hospital admissions, and emergency room visits in hospitals because of cardiovascular, respiratory, and other diseases (2 9). Other studies have shown that high levels of air pollution increase morbidity and mortality rates (10).…”
Section: Introductionmentioning
confidence: 99%